The effects of rhythmic exercise using PNF patterns on gait variables in normal adults - Gong, Wontae (Technology and health care, 2024)
BACKGROUND: Maintaining gait stability is an important factor for preventing falls of normal adults. Thus, it is necessary to conduct research on gait variables in normal adults. OBJECTIVE: In this study, we conducted research on the effect of rhythmic exercise using proprioceptive neuromuscular facilitation (PNF) patterns on gait variables in normal adults. METHODS: Thirty-two subjects were divided into two groups, the training and control groups, with 16 subjects in each group. We measured various gait variables step time difference (STD), step length difference (SLD), single support difference (SSD), stance phase difference (STPD) and swing phase difference (SWPD) for the pre-test and post-test in each group. RESULTS: As a result of paired t-tests on various gait variables (STD, SLD, SSD, STPD, SWPD) of the training and control group, the training group showed significance in SLD, STPD and STD and the control group had no significance in all items. CONCLUSIONS: In this study, which verified the effect of rhythmic exercise using the PNF patterns on the gait variables of normal adults, there was statistical significance in SLD, STPD, and STD showing that dynamic exercise using the PNF pattern is helpful in improving the walking ability of normal adults.